A 3-D human model of complex cardiac arrhythmias. (15th September 2021) - Williams, Kenneth; Liang, Timothy; Massé, Stéphane; Khan, Safwat; Hatkar, Rupal; Keller, Gordon; Nanthakumar, Kumaraswamy; Nunes, Sara S.
Abstract: Cardiac arrhythmias impact over 12 million people globally, with an increasing incidence of acquired arrhythmias. Although animal models have shed light onto fundamental arrhythmic mechanisms, species-specific differences and ethical concerns remain. Current human models using human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) either lack the higher order tissue organization of the heart or implement unreliable arrhythmia induction techniques. Our goal was to develop a robust model of acquired arrhythmia by disrupting cardiomyocyte cell-cell signaling – one of the hallmarks of complex arrhythmias. Human 3D microtissues were generated by seeding hydrogel-embedded hiPSC-CMs and cardiac fibroblasts into an established microwell system designed to enable active and passive force assessment. Cell-cell signaling was disrupted using methyl-beta cyclodextrin (MBCD), previously shown to disassemble cardiac gap junctions. We demonstrate that arrhythmias were progressive and present in all microtissues within 5 days of treatment. Arrhythmic tissues exhibited reduced conduction velocity, an increased number of distinct action potentials, and reduced action potential cycle length. Arrhythmic tissues also showed significant reduction in contractile force generation, increased beating frequency, and increased passive tension and collagen deposition, in line with fibrosis. A subset of tissues with more complex arrhythmias exhibited 3D spatial differences in action potential propagation. Pharmacological and electrical defibrillation was successful. Transcriptomic data indicated an enrichment of genes consistent with cardiac arrhythmias. MBCD removal reversed the arrhythmic phenotype, resulting in synchronicity despite not resolving fibrosis. This innovative & reliable human-relevant 3D acquired arrhythmia model shows potential for improving our understanding of arrhythmic action potential conduction and furthering therapeutic development. Statement of significance: This work describes a 3D human model of cardiac arrhythmia-on-a-chip with high reproducibility, fidelity, and extensive functional applicability. To mimic in vivo conditions, human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) and cardiac fibroblasts from healthy controls were combined in a biocompatible fibrin hydrogel and seeded between two deflectable polymeric rods. Using the innate functional properties of this 3D model as well as advanced optical imaging techniques we demonstrated dramatic changes in contraction rate, synchronicity, and electrophysiological conduction in arrhythmic tissues relative to controls. Taken together, these data demonstrate the distinctive potential of this new model for pathophysiological studies, and for arrhythmia drug testing applications. Graphical abstract: Image, graphical abstract